2022
DOI: 10.2196/26299
|View full text |Cite
|
Sign up to set email alerts
|

Unit Response and Costs in Web Versus Face-To-Face Data Collection: Comparison of Two Cross-sectional Health Surveys

Abstract: Background Potential is seen in web data collection for population health surveys due to its combined cost-effectiveness, implementation ease, and increased internet penetration. Nonetheless, web modes may lead to lower and more selective unit response than traditional modes, and this may increase bias in the measured indicators. Objective This research assesses the unit response and costs of a web study versus face-to-face (F2F) study. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…a difference of 11%). This is in line with previous studies showing that people with a higher socio-economic background are more likely to participate [22][23][24]. In light of these findings, it is advisable to include education in the sampling scheme.…”
Section: Discussionsupporting
confidence: 90%
“…a difference of 11%). This is in line with previous studies showing that people with a higher socio-economic background are more likely to participate [22][23][24]. In light of these findings, it is advisable to include education in the sampling scheme.…”
Section: Discussionsupporting
confidence: 90%
“…A major limitation of this study is the low response rate. Web-based surveys are known to have a significantly lower response rate than paper-based [ 16 ]. A Danish randomised study showed a risk difference of 55.3% in response rate for the internet group compared to the paper-based for a survey distributed to patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, survey findings indicated that the mental health of refugees and migrants during the COVID-19 pandemic was significantly impacted, particularly for certain subgroups (i.e., insecure housing situation and residence status) who reported experiencing higher levels of increased discrimination and increases in daily life stressors [75]. To target vulnerable groups, such as less educated people or people of foreign origin, it is better to opt for other data collection techniques such as interview-driven data collection [76].…”
Section: Strengths and Limitationsmentioning
confidence: 99%